On language profile of V. Akulenko: spontaneous speech characteristics - Малиновська, Ірина Віталіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
This essay is a second in a series of publications attempting to portray professor V. Akulenko’s language personality. Analyzed have been a number of reconstructed fragments of his oral monologues and dialogue remarks as per their lingual and rhetorical characteristics. Three types of communicative situations were chosen: academic, administrative and everyday life. A procedure of the selection and reconstruction of fragments was elaborated on the basis of the Peer Review Method. Consideration has been given to social parameters of speech, emotional state of the speaker, as well as pragmatic situation of communication.